ALK‐rearranged histiocytosis: Report of two cases with involvement of the central nervous system. (18th June 2021) - Rossi, Sabrina; Gessi, Marco; Barresi, Sabina; Tamburrini, Gianpiero; Giovannoni, Isabella; Ruggiero, Antonio; Colafati, Giovanna Stefania; Frassanito, Paolo; Carboni, Alessia; Alexandre, Andrea; Cacchione, Antonella; Trombatore, Pietro; et al.
Abstract: Aims: Histiocytoses are a heterogeneous group of localized or disseminated diseases. Clinical presentation and patients' outcome vary greatly, ranging from mild to life‐threatening disorders. Rare cases of systemic or localized histiocytosis harboring ALK rearrangement have been reported. Methods: Two cases of CNS histiocytosis were thoroughly investigated by implementing multiple molecular tests, i.e. FISH, RT‐qPCR, NGS analysis. Results: In a 10‐month old girl (patient #1), MRI showed two left hemispheric lesions and a right fronto‐mesial lesion histologically consisting of a moderately cellular infiltrative proliferation, composed by CD68(PGM1)+/CD163+ spindle cells. ALK 5'/3'‐imbalance and a KIF5B(exon 24)‐ALK(exon 20) fusion were documented by RT‐qPCR and NGS analysis, respectively. A subsequent CT scan showed multiple hepatic and pulmonary lesions. The patient was started on chemotherapy (vinblastine) associated to an ALK‐inhibitor (Alectinib) with remarkable response. In a 11‐year‐old girl (patient #2), MRI showed a right frontal 1.5 cm lesion. Neuropathological examination revealed a histiocytic proliferation composed by medium sized CD68(PGM1)+/HLA‐DR+ cells, showing moderate ALK1 positivity. ALK rearrangement and a KIF5B(exon 24)‐ALK(exon 20) fusion were demonstrated also in this case. Subsequent CT, 18F‐FDG‐PET and MRI scans showed the presence of a single right femoral lesion, proved to be a fibrous cortical defect. Conclusions: In ALK‐histiocytoses, CNS involvement may occur as part of a systemic disease or, rarely, as its only primary disease localization, which could remain otherwise asymptomatic. The diagnosis often relies on neuropathological examination of brain biopsy, which may pose a diagnostic challenge due to the variable histopathological features. An integrated histological and molecular approach in such cases is recommended. Abstract : CNS ALK ‐rearranged histiocytosis.